Pentecostalism and inter-religious dialogue: a case study of the Apostolic Faith Mission (AFM) in Zimbabwe and Shona traditional religion - Sipeyiye, Macloud (Cambridge Scholars Publishing, 2018)
The fragile economies and political climates of the developing world have created a confidence vacuum. In such circumstances, people tend to feel insecure and lose their bearings, leading to alarming levels of desperation for answers to questions about their security and survival. Religion becomes handy and wields great potential for proffering solutions but is characterised by a diversity or pluralism that, instead of providing solutions, can in fact open a platform for new dimensions of contestation that stifle cohesion, solidarity and harmony as religions fight for control, influence and survival. The competitive mode often assumed by some religions in such situations is a slap in the face of the spirit of interreligious dialogue. Pentecostal Christianity, for example, grows fastest among groups of people who find in it both a vision for themselves and a means of support for their families. As noted by Maldonado (1993: 235) and quoted by Davie (2007: 25), “Pentecostal communities become in a very practical sense, havens and way stations in the journey up the socioeconomic ladder.”